PAPARAN EKSTRAK TERIPANG PASIR (Holothuria scabra) TERHADAP GAMBARAN HISTOPATOLOGI HATI MENCIT (Mus musculus) - Yosep Matruty; Theopilus Watuguly (BIOPENDIX, 2016)
Background: In Indonesia, traditionally sea cucumber (Holothuria scabra) is often used as a cure gout. The purpose of the research is to determine the effects of sea cucumber (Holothuria scabra) extracts against liver histopathology picture mice (Mus musculus). Method: Mice used were male mice as much as 15 tails and were divided into 5 groups. Each group consisted of three mice. Group I as a positive control given allopurino l0.1%. The second group was given distilled water as a negative control. Group III, IV and V as the treatment group was given sea cucumber extract with each concentration of 5%, a concentration of 10% and 15% concentration. Result: The results were analyzed quantitatively, showed that the administration of potassium bromate showed the presence of fatty and necrosis. But after being given a sea cucumber extract with a concentration of 10% and a concentration of 15% still showed the presence of inflammatory cells and remnants of fatty liver (same as the picture of liver histopathology in the positive control). At a concentration of 5% normal liver histopathology same as the picture of liver histopathology in the negative control. Conclution: Sea cucumbers with a concentration of 5% can be used as a gout medicine without any side effects for conditions onal liver function.